2023
DOI: 10.1093/cvr/cvad087
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lncRNA links endothelial glycocalyx to vascular dysfunction of tyrosine kinase inhibitor

Abstract: Aims Novel cancer therapies leading to increased survivorship of cancer patients have been negated by a concomitant rise in cancer therapies-related cardiovascular toxicities. Sunitinib, a first line multi receptor tyrosine kinase inhibitor (TKI), has been reported to cause vascular dysfunction although the initiating mechanisms contributing to this side effect remain unknown. Long non-coding RNAs (lncRNAs) are emerging regulators of biological processes in endothelial cells (ECs); however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…The endothelial glycocalyx played a vital role in safeguarding the vascular endothelial barrier function. However, previous research indicated that ADAMTS5 could compromise the endothelial glycocalyx, leading to vascular endothelial dysfunction . To study the role of ADAMTS5 in the dysfunction of the barrier, we determined the expression of syndecan-1, which represented a major breakdown product of the glycocalyx, and hyaluronic acid in the CSF from HIV-negative patients with neurosyphilis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The endothelial glycocalyx played a vital role in safeguarding the vascular endothelial barrier function. However, previous research indicated that ADAMTS5 could compromise the endothelial glycocalyx, leading to vascular endothelial dysfunction . To study the role of ADAMTS5 in the dysfunction of the barrier, we determined the expression of syndecan-1, which represented a major breakdown product of the glycocalyx, and hyaluronic acid in the CSF from HIV-negative patients with neurosyphilis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research had highlighted the capacity of ADAMTS5 to degrade the endothelial glycocalyx, an essential structure within the extracellular matrix of vascular endothelial cells. 23 The endothelial glycocalyx comprised a network of glycoproteins, proteoglycans, and hyaluronic acid lining the luminal surface of endothelial cells. 33,34 Notably, the glycocalyx of BBB played a critical role in various fundamental physiological functions, including the regulation of vascular permeability, inflammation, coagulation, and the synthesis of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations